2018
DOI: 10.1002/anie.201809676
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Helical Nanostructures with Controllable Handedness in Bulk Diblock Copolymers

Abstract: Double-helical nanostructures with controllable handedness in bulk materials is of high interest in science and technology for the design and fabrication of new materials, in particular metamaterials, which mimic their natural homologues or even show superior properties. Herein, we report the fabrication of double-helical structures with controlled handedness through the self-assembly of an achiral diblock copolymer doped with d- and l-tartaric acid (TA). The helices showed clear handedness dependence on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…The chiral nanostructures based on self‐assembly and hierarchical chirality transfer can be used as nanotemplates for the preparation of inorganic or metallic functional materials with chiral microstructures. [ 44b,c,e,46–48,76 ] The transfer and amplification of chirality from molecular scale to aggregation level can enhance the chiral properties, providing a stereo‐geometrical environment or chiral space and endowing them with special functions such as chiral sensing, chiral separation, asymmetry catalysis, and several bio‐effects. Moreover, photonic and plasmonic properties with chiral features can also be achieved by fabricating the chiral arrangement of inorganic or metal nanoparticles based on supramolecular chirality transfer and hierarchical self‐assembly, or combined with novel top‐down approaches when necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chiral nanostructures based on self‐assembly and hierarchical chirality transfer can be used as nanotemplates for the preparation of inorganic or metallic functional materials with chiral microstructures. [ 44b,c,e,46–48,76 ] The transfer and amplification of chirality from molecular scale to aggregation level can enhance the chiral properties, providing a stereo‐geometrical environment or chiral space and endowing them with special functions such as chiral sensing, chiral separation, asymmetry catalysis, and several bio‐effects. Moreover, photonic and plasmonic properties with chiral features can also be achieved by fabricating the chiral arrangement of inorganic or metal nanoparticles based on supramolecular chirality transfer and hierarchical self‐assembly, or combined with novel top‐down approaches when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Furthermore, Lu et al fabricated doublehelical nanostructures by replacing the achiral BC with poly(1,4butadiene)-b-poly(ethylene oxide) (PBd-b-PEO) using such a doping method. [46] One strength of this chiral doping strategy is that the dopant can be easily removed by solvents, while the asymmetric phase structures can be memorized after the removal of dopants. Based on this method, the chiral arrangement of gold nanoparticles with both single helical structures and double helical structures were successfully obtained.…”
Section: Asymmetric Phase Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Lu et al successfully fabricated double helices with controlled handedness via the self-assembly of an achiral BCP induced by D-and L-tartaric acid. 33 Considering that no chiral factor was introduced in our PISA formulation, it can be rationally concluded that the helical nanostructure was not caused by chirality amplication. We speculated that the TFEMA unit within the stabilizer block led to the formation of helical nanowires.…”
Section: Resultsmentioning
confidence: 95%